Dynamics and performance of surface finish measurement styli - Duckworth, Greg (2020)
The main aim of this project was to characterise measurement stylus dynamic performance prior to manufacture and application. This work investigated each area of stylus production, and its influence of the dynamic performance of the stylus. The literature surrounding stylus dynamics and the wider performance of measurement instrumentation is sparse, with much of the development being undertaken in private.